GROWTH PERIOD OF LENTIL VARIETIES AND RANGES - Jabarov F.O. (European Journal of Agricultural and Rural Education, 2024)
This article presents information about the duration of the growing season of 30 varieties and ridges of lentils (Lens culinaris) studied in a controlled variety trial nursery under the conditions of rainy fields, compared with the model variety.